Development of a multiplex RT-PCR method for the detection of four porcine enteric coronaviruses - Niu, Jia-Wei; Li, Jin-Hui; Guan, Jin-Lian; Deng, Ke-Hui; Wang, Xiu-Wu; Li, Gen; Zhou, Xia; Xu, Min-Sheng; Chen, Rui-Ai; Zhai, Shao-Lun; He, Dong-Sheng (Frontiers in Veterinary Science, 2022)
Porcine enteric coronaviruses are pathogens that cause viral diarrhea in pigs and are widely prevalent worldwide. Moreover, studies have shown that some porcine enteric coronaviruses can infect humans and poultry. In order to effectively monitor these viruses, it is necessary to establish a multiple detection method to understand their prevalence and conduct in-depth research. Common porcine enteric coronaviruses include Porcine epidemic diarrhea virus (PEDV), Porcine transmissible gastroenteritis virus (TGEV), Porcine delta coronavirus (PDCoV), and Swine acute diarrhea syndrome coronavirus (SADS-CoV). Pigs infected with these viruses have the common clinical symptoms that are difficult to distinguish. A quadruplex RT-PCR (reverse transcription-polymerase chain reaction) method for the simultaneous detection of PEDV, PDCoV, TGEV and SADS-CoV was developed. Four pairs of specific primers were designed for the PEDV M gene, PDCoV N gene, TGEV S gene and SADS-CoV RdRp gene. Multiplex RT-PCR results showed that the target fragments of PDCoV, SADS-CoV, PEDV and TGEV could be amplified by this method. and the specific fragments with sizes of 250 bp, 368 bp, 616 bp and 801 bp were amplified, respectively. This method cannot amplify any fragment of nucleic acids of Seneca Valley virus (SVV), Porcine Reproductive and Respiratory Syndrome Virus (PRRSV) and Atypical Porcine Pestivirus (APPV), and has good specificity. The lowest detection limits of PDCoV, PEDV, TGEV and SADS-CoV were 5.66 × 105 copies/μL, 6.48 × 105 copies/μL, 8.54 × 105 copies/μL and 7.79 × 106 copies/μL, respectively. A total of 94 samples were collected from pig farms were analyzed using this method. There were 15 positive samples for PEDV, 3 positive samples for mixed infection of PEDV and PDCoV, 2 positive samples for mixed infection of PEDV and TGEV, and 1 positive sample for mixed infection of PEDV, TGEV, and PDCoV. Multiplex RT-PCR method could detect four intestinal coronaviruses (PEDV, PDCoV, TGEV, and SADS-CoV) in pigs efficiently, cheaply and accurately, which can be used for clinical large-scale epidemiological investigation and diagnosis.